1990
DOI: 10.1111/j.1445-2197.1990.tb07516.x
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticojejunostomy Versus Pancreaticogastrostomy in Reconstruction Following Pancreaticoduodenectomy

Abstract: Nineteen consecutive patients, 7 male and 12 female, underwent pancreaticoduodenectomy for malignancy during the 3‐year period 1985‐88. The pancreatic remnant in the first 12 patients (Group 1) was managed alternately by pancreaticojejunostomy (PJ) and pancreaticogastrostomy (PG). Patients undergoing PJ and PG (6 each) were comparable in age, biochemical parameters and nature and extent of disease. Three patients, all in the PJ subgroup, died (25% mortality) due to pancreatic leak, biliary leak and hepatocellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 12 publications
1
13
0
1
Order By: Relevance
“…Many retrospective studies support our finding of a reduced rate of anastomotic leak when a PG is used 28,29 . Other potential advantages of PG over PJ reported by non‐randomized studies but not confirmed by our own include reduced mortality, 29–31 reoperation, 28,30 DGE, 30 bile leak 30 and length of stay 28 . Two randomized trials have compared PG to PJ with respect to postoperative outcomes.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Many retrospective studies support our finding of a reduced rate of anastomotic leak when a PG is used 28,29 . Other potential advantages of PG over PJ reported by non‐randomized studies but not confirmed by our own include reduced mortality, 29–31 reoperation, 28,30 DGE, 30 bile leak 30 and length of stay 28 . Two randomized trials have compared PG to PJ with respect to postoperative outcomes.…”
Section: Discussionsupporting
confidence: 63%
“…The major source of morbidity and potential mortality after surgery is pancreatic fistula, which is caused by difficulties associated with the pancreatic anastomosis. Pancreaticogastrostomy (PG) has become popular in many centres as an alternative to pancreaticojejunostomy (PJ) 28–35 …”
Section: Introductionmentioning
confidence: 99%
“…Overall, 26 articles describing 3,752 patients were identified for the meta-analysis: 22 OCSs (n = 3, 199 patients) [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] and 4 RCTs (n = 553 patients) [10,57,58,59]. A total of 1,922 patients underwent PG (RCTs n = 276 patients, OCSs n = 1,646 patients), whilst 1,830 patients underwent PJ (RCTs n = 277 patients, OCSs n = 1,553 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Duffas et al [58] preferred using internal pancreatic ductal stents in their RCT, whilst Fernández-Cruz et al [10] also used similar internal ductal stents consistently in their patients. Eight OCSs reported the use of pancreatic ductal stent in some of patients at the surgeons' discretion [35,36,43,47,51,53,55,56]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared pancreaticojejunostomy (PJ) and pancreaticogasrostomy (PG) with respect to the incidence of POPF. Published single institutional studies have favored PG over PJ [8,9]. A large meta-analysis has shown a significantly lower incidence of pancreatic fistula after PG as compared to end-to-end or end-to-side PJ [10].…”
Section: Introductionmentioning
confidence: 99%